The correlation among plagiarism awareness, genders, and essay writing skills of English education of postgraduate students of Sultan Ageng Tirtayasa university - John Pahamzah; Hanifah Andriani; Nurhaedah Gailea; Akhmad Baihaqi (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2022)
Writing scientific papers is influenced by several things, including grammatical problems, linguistic problems, technical aspects of writing, and plagiarism aspect. Gender factors are indicated to contribute to plagiarism behavior because men and women are assumed to have different attitudes and style in perceiving an idea. This study aims to obtain the correlation among the plagiarism awareness, gender, the expository essay of the capability in composing it. This study uses a quantitative approach with the correlational method. Questionnaires and composing of the text tests were conducted to get the results of the research. Research respondents were 24 postgraduate students at Sultan Ageng Tirtayasa University of Postgreaduate Program of English Education, consisting of 12 males and 12 females. From the data analysis, it was found that: First, the relationship between plagiarism awareness and expository essay writing skills is 0.783 ( 0.05). It means that there was no tight relation among plagiarism alarming of expository essay writing skills. Second, the tight relation among gender and expository essay composing skills is 0.783 ( 0.05). That is, gender also does not provide a significant contribution to the skill of writing an expository essay. Third, the value of R square among students' plagiarism awareness (X1), gender (X2), and expository essay writing skills (Y) is 0.011 (1.1%). It means that expository essay writing skills are influenced by awareness of plagiarism and different category by 1.1% and 98.9% is affected by different variations. Although the contribution is low, these variations played significant roles in expository essay composing skills. Therefore, student awareness needs to be increased by implementing strict plagiarism policies in universities.Keywords: plagiarism awareness, gender, writing skill, expository essay Korelasi antara kesadaran plagiarisme, gender, dan keterampilan menulis esai ekspositori pada mahasiswa bahasa Inggris Pascasarjana Universitas Sultan Ageng TirtayasaAbstrakMenulis karya ilmiah sangat dipengaruhi oleh beberapa hal, seperti tata bahasa, linguistik, aspek teknis penulisan, dan hal plagiarisme. Faktor-faktor yang mempengaruhi seperti gender diindikasikan berkontribusi dalam perilaku plagiarisme, karena pada faktanya, laki-laki dan perempuan diasumsikan memiliki sikap berbeda dalam mempersepsi suatu ide. Penelitian ini bertujuan mendeskripsikan hubungan antara kesadaran plagiarisme, jenis kelamin, dan keterampilan menulis esai ekspositori. Penelitian ini menggunakan pendekatan kuantitatif dengan mengimplementasikan sub desain penelitian korelasional. Dalam proses pengumpulan data, peneliti menggunakan instrumen penelitian berupa angket dan tes kemampuan menulis. Responden penelitian adalah 24 mahasiswa Pascasarjana Universitas Sultan Ageng Tirtayasa, yang terdiri atas 12 laki-laki dan 12 perempuan. Dari hasil pembahasan hasil penelitian dapat disimpulkan beberapa hal. Pertama, hubungan kesadaran plagiarisme dengan keterampilan menulis esai ekspositori sebesar 0,783 ( 0,05). Artinya, tidak ada hubungan antara kesadaran plagiarisme dengan keterampilan menulis esai ekspositori. Kedua, hubungan jenis kelamin dengan keterampilan menulis esai ekspositori sebesar 0,783 ( 0,05). Artinya, jenis kelamin tidak memberikan kontribusi yang signifikan terhadap keterampilan menulis esai ekspositori. Ketiga, nilai R square antara kesadaran plagiarisme siswa (X1), jenis kelamin (X2), dan keterampilan menulis esai ekspositori (Y) sebesar 0,011 (1,1%). Artinya, keterampilan menulis esai ekspositori dipengaruhi oleh kesadaran plagiarisme dan gender sebesar 1,1%, sedangkan 98,9% dipengaruhi oleh variabel lain. Meskipun kontribusinya rendah, kedua variabel tersebut tetap berperan dalam keterampilan menulis esai ekspositori. Oleh karena itu, kesadaran mahasiswa perlu ditingkatkan dengan penerapan kebijakan plagiarisme yang tegas di perguruan tinggi.Kata Kunci: kesadaran plagiarisme, gender, keterampilan menulis, esai ekspositori